Optimalisasi Pembelajaran Interaktif melalui Pengembangan Modul Ajar Digital Berbasis Flip HTML5 untuk Mata Pelajaran Produktif di Sekolah Menengah Kejuruan - Erlanda, Rendi; A, Yufrizal; K, Arwizet; Prasetya, Febri (TSAQOFAH, 2024)
Vocational education, as a specialised form of education, is designed to prepare students with practical and theoretical skills in various fields of technical, technological, and business expertise, in accordance with the demands of the labour market. The use of teaching modules in the PDTM class X Machining Engineering subject is not optimal, causing the learning process to be less effective. This study aims to develop a FlipHTML5-based PDTM teaching module at SMK Negeri 2 Banda Aceh, adopting the R&D development model with reference to the 4D model. The steps of the 4D model include definition, design, development, and dissemination. Research data were obtained through a questionnaire validation sheet, and data analysis using quantitative descriptive statistical methods with Aiken's V formula. The results showed that the developed module was feasible as a self-learning media. The validity of material experts reached (∑V) 0.842, and media experts reached (∑V) 0.909, with valid criteria. Based on the validity assessment, this PDTM learning module for class X Machining Engineering can be concluded as a feasible additional learning media for students.